Experience with viral hepatitis C treatment among people who inject drugs and participate in a methadone substitution treatment program - Krekulová, L; Vavrinčíková, L (Epidemiologie, mikrobiologie, imunologie, 2021)
OBJECTIVES: Long-term monitoring of the mutual effects of chronic viral hepatitis C (VHC) treatment and tailored addiction treatment. In 2016, the World Health Organization (WHO) published an action plan to eliminate viral hepatitis C globally by 2030. People who inject drugs (PWID) are a key population that needs increased attention and care. Two decades before the announcement of the WHO plan for the global elimination of HCV (hepatitis C virus), the Remedis Medical Facility, where the study was conducted, established a “Comprehensive Care Program for patients with substance use disorders and addictive behaviour”. METHODS: We evaluated all patients who were in the methadone program as of 1 March 2020, regardless of OST duration, OST dosage, age or gender. Their epidemiological and demographic data obtained during a structured clinical interview and laboratory test results were analysed. RESULTS: Of 24 patients on methadone substitution therapy, 12 (50%) were anti-HCV negative before starting OST. None of them became newly infected with hepatitis C virus (HCV) during OST. The remaining 12 of the study patients were anti-HCV positive. Ten of them have already undergone successful treatment for viral hepatitis. Two patients were re-infected with HCV. CONCLUSION: The presented work confirms the high efficacy of chronic VHC treatment among PWID in inducing suitable conditions. We consider combination of HCV infection treatment and targeted tailored addiction treatment as a starting point for achieving control over the HCV epidemic in the Czech Republic, with a possible positive impact on other blood-borne infections related to risky behaviour.
Keywords: antivirové látky; HCV (hepatitis C virus); VHC (viral hepatitis C); Pharmaceutical Preparations; léčivé přípravky; PWID (People Who Injected Drugs); Opiate Substitution Treatment; Humans; opiátová substituční terapie; lidé; Czech Republic; methadon; Remedis, Prague; MTD (methadone); World Health Organization; OST (opioid substitution treatment); Světová zdravotnická organizace; Substance Abuse, Intravenous; Methadone; hepatitida C; Antiviral Agents; Hepatitis C; Česká republika; intravenózní abúzus drog